Predicting discharge and sediment for the Abay (Blue Nile) with a simple model - Steenhuis, Tammo S.; Collick, A.S.; Easton, Z.M.; Leggesse, E.S.; Bayabil, H.K.; White, E.D.; Awulachew, Seleshi Bekele; Adgo, E.; Ahmed, A.A. (Wiley, 2009)
Models accurately representing the underlying hydrological processes and sediment dynamics in the Nile Basin are necessary for optimum use of water resources. Previous research in the Abay (Blue Nile) has indicated that direct runoff is generated either from saturated areas at the lower portions of the hillslopes or from areas of exposed bedrock. Thus, models that are based on infiltration excess processes are not appropriate. Furthermore, many of these same models are developed for temperate climates and might not be suitable for monsoonal climates with distinct dry periods in the Nile Basin. The objective of this study is to develop simple hydrology and erosion models using saturation excess runoff principles and interflow processes appropriate for a monsoonal climate and a mountainous landscape. We developed a hydrology model using a water balance approach by dividing the landscape into variable saturated areas, exposed rock and hillslopes. Water balance models have been shown to simulate river flows well at intervals of 5 days or longer when the main runoff mechanism is saturation excess. The hydrology model was developed and coupled with an erosion model using available precipitation and potential evaporation data and a minimum of calibration parameters. This model was applied to the Blue Nile. The model predicts direct runoff from saturated areas and impermeable areas (such as bedrock outcrops) and subsurface flow from the remainder of the hillslopes. The ratio of direct runoff to total flow is used to predict the sediment concentration by assuming that only the direct runoff is responsible for the sediment load in the stream. There is reasonable agreement between the model predictions and the 10-day observed discharge and sediment concentration at the gauging station on Blue Nile upstream of Rosaries Dam at the Ethiopia-Sudan border.